Colleges Of Education Lecturers’ Self-Efficacy On The Integration Of Ict For Instruction In Oyo State, Nigeria - Omolafe Ebenezer; Issa Ahmed Idris; Ajila Musa Alabi; Adefuye Adetayo Linus; Aderoju Musiliyu Adekola (Indonesian Journal of Basic Education, 2023)
This study examined the lecturers’ self-efficacy on the integration of Information and Communication Technology (ICT) for instruction. A descriptive research design of the survey type was adopted for this study, the population for this study were all colleges of education lecturers’ in Oyo State, three colleges of education were purposively selected, the target population were colleges of education lecturers’ in the selected colleges, a researcher designed questionnaire was used to collect data from the respondents, data gathered was analyzed using descriptive and inferential statistics; frequency count and percentage was used to organized the demographic information and provide answers to the research question, hypotheses 1 was tested using t-test while hypotheses 2 and 3 were tested using ANOVA at 0.05 level of significance. The findings were: College of Education (COE) lecturers can integrate ICT for instruction; COE lecturers faced challenges while integrating ICT for instruction; there was a significant difference in male and female lecturers’ self-efficacy on the integration of ICT for instruction; level of experience had no significant impact on the integration of ICT for instruction and qualifications had significant impact on the integration of ICT for instruction among the sampled lecturers. The study concluded that majority of lecturers in colleges of education in Oyo State were not ready to integrate ICT into instruction. Nevertheless, lack of technology integration know-how still hinders the integration of ICT for instruction. This implied that lecturers integrating of ICT for instruction would improve their teaching and learning process. The study recommended that; COE lecturers should encourage on the further benefits of using ICT for instruction.